Case of Metastatic Canine Transmissible Venereal Tumor in a Dog: Clinical and Cytological Evaluation - Olaifa, Olanrewaju Samuel; Usman, Abdulrauf Adekunle; Adebiyi, Taiwo Kemi; Ogunro, Bamidele Nyemike; Osereime, Adah; Antia, Richard Edem; Ajibade, Favour Akinfemi; Adeshubomi, Ojuolape Adeyemi; Soneye, Toluwalase Oluwatimilehin (Universitas Airlangga, 2025)
Canine transmissible venereal tumor (TVT) is a naturally occurring, transmissible neoplasm primarily affecting the genitalia in dogs. Though generally benign, it can rarely metastasize to other body parts. This report describes a rare case of metastatic TVT in a 2-year-old female Boerboel, presenting with a large, ulcerated vulvar mass and metastases to the popliteal lymph node and mammary glands. Clinical findings included progressive mass growth, emaciation, and systemic symptoms. Hematological tests revealed non-regenerative anemia and elevated white blood cell count, while cytological examination identified neoplastic round cells with high nucleus-to-cytoplasm ratios and mitotic figures. The dog was treated with vincristine chemotherapy, metronidazole, vitamin C, and a diet supplemented with crude sap extract of Telfairia occidentalis at 120 mg/kg once daily. Significant tumor regression and clinical improvement were observed after four weeks, although persistent anemia and borderline hypoproteinemia were noted. By the fifth week, the mass had notably reduced, and the dog's condition continued to improve, though some hemorrhage remained. This case highlights the rare occurrence of metastatic TVT and underscores the effectiveness of vincristine in treatment, emphasizing the need for prompt diagnosis and management despite its generally low metastatic rate.